Lactiplantibacillus plantarum ST-III-fermented milk improves autistic-like behaviors in valproic acid-induced autism spectrum disorder mice by altering gut microbiota - Zhang, Yilin; Guo, Min; Zhang, Hongfa; Wang, Yuezhu; Li, Ruiying; Liu, Zhenmin; Zheng, Huajun; You, Chunping (Frontiers in Nutrition, 2022)
Introduction Autism spectrum disorder (ASD) is a serious neurodevelopmental disorder with a rising incidence. More and more studies have shown that abnormal microbiota composition may aggravate the behavioral symptoms and biological signs of ASD, and interventions of probiotics and diet have emerged as a potential improvement measure. Methods Lactiplantibacillus plantarum ST-III-fermented milk was applied as an oral intervention in a valproic acid (VPA)-induced ASD mice model, and the effect of probiotic intake on autistic-related behaviors and gut microbiota composition was evaluated by behavioral tests and 16S rRNA gene sequencing. Results Gender specificity was shown in VPA-induced behavioral abnormalities in a mouse model, and L. plantarum ST-III-fermented milk was effective in ameliorating the impaired social interaction in male ASD mouse models, but not for the anxiety behavior exhibited by female ASD mouse models. Meanwhile, dietary changes were found to be the main cause of the altered gut microbiota in mice, and additional intake of L. plantarum ST-III-fermented milk seemed to improve autistic-like behaviors in male ASD mouse models by modulating specific gut microbes. Discussion These findings suggest that L. plantarum ST-III-fermented milk may play a beneficial role in improving the behavioral symptoms of ASD and is expected to be one of the candidate functional foods for ASD.